Parable and politics in early Islamic history : the Rashidun caliphs - El-Hibri, Tayeb (Columbia University Press, 2010)
The story of the succession to the Prophet Muhammad and the rise of the Rashidun Caliphate (632-661 AD) has been familiar to historians from the political histories of medieval Islam, which lend a factual credibility to scholarly narratives, and the competing perspectives of Sunni and Shi'i Islam, which focus on the legitimacy of their claims. While descriptive and varied, these approaches have long excluded a third reading in which the conflict over the succession to the Prophet is treated as a parable, the motives, sayings, and actions of the protagonists revealing profound links to.